Multilayered Sporadic‐E Response to the Annular Solar Eclipse on June 21, 2020. Issue 3 (5th March 2021) - Wang, Jin; Zuo, Xiaomin; Sun, Yang‐Yi; Yu, Tao; Wang, Yungang; Qiu, Lihui; Mao, Tian; Yan, XiangXiang; Yang, Na; qi, Yifan; Lei, Jiuhou; Sun, Lingfeng; et al.
Abstract: A moon shadow of annular solar eclipse passed through East Asia in the afternoon on June 21, 2020, which was a good opportunity to study the rapid ionospheric response to the solar radiation variations. In the study, the high‐frequency echoes recorded by the ionosondes at Wuhan (82.4% obscuration), Xiamen (97.8% obscuration), and Nanning (81.1% obscuration) are analyzed to examine the variations in sporadic‐ E ( E s ) during the obscuration over the East China area. The echoes show not only the variations in the typical signal E s layer below 130 km, but for the first time also the multilayered E s at much higher altitudes (130–190 km) during the eclipse. Specifically, the multilayered E s is only observed over Nanning, while different E s behaviors are observed in the other two stations. The relationship between the formation of the multilayered E s and the uplifted E s near the center path of the moon shadow are examined in the study. The small‐scale atmospheric gravity waves play a key role in modulating the E s behaviors during the eclipse. Plain Language Summary: The sky's darkness due to the eclipse obscuration can reduce the air temperature and induce wind and atmospheric waves, which makes a bit windy and chill people suddenly during the obscuration. Following the famous total solar eclipses on July 22, 2009 and August 21, 2017, the annular solar eclipse occurred on June 21, 2020 is another wonderful opportunity for us to examine the ionospheric and atmospheric responses to the sudden darkness. The impact of the annular solar eclipse on the ionosphere and atmosphere shall be weaker than that of a total solar eclipse. However, it is surprising for us to see that the ionospheric behaviors between 100 and 200 km altitudes during the 2020 annular eclipse are as prosperous as those during the total solar eclipses. The morphology of sporadic‐E (Es) during the annular solar eclipse is examined here in detail. The results reveal that the atmospheric gravity waves and the transport process mainly control the Es behaviors over eastern China during the 2020 annular solar eclipse. Key Points: The unexpected multilayered Es is observed by the ionosonde over Nanning (southern 81.1% obscuration) after the maximum obscuration The occurrence of small‐scale AGWs due to the eclipse should result in the multilayered Es at altitudes from 130 to 190 km The Es layer uplifts significantly over Xiamen (97.8% obscuration) near the maximum obscuration